O processo de internacionalização de empresas da China: estratégias empresariais e diplomacia econômica - Oliveira, Mariana Sandoval de (2013)
The dissertation will examine the internationalization of a group of major Chinese companies, aiming to characterize the process of internationalization and its goals and to answer to what extent the process can be explained by the usual standards of large companies around the world and to what extent the process follows, accompanies or is strongly conditioned by the state goals, as part of Chinese economic diplomacy. The hypothesis is that the internationalization of large Chinese companies are oriented towards ensuring access to and supply of ores, fuel and food, an issue vital to the security of China, as well as providing the domain of complex technological processes, a topic of great relevance to the objectives China's rise and consolidation of its development. The dissertation will also examine the instruments of state support for the internationalization of Chinese companies in order to determine their relevance for Chinese companies in the sample. It also seeks to examine China's economic diplomacy and its possible implications for the internationalization strategies of companies